2017
DOI: 10.3390/jcm6050053
|View full text |Cite
|
Sign up to set email alerts
|

The Soft- and Hard-Heartedness of Cardiac Fibroblasts: Mechanotransduction Signaling Pathways in Fibrosis of the Heart

Abstract: Cardiac fibrosis, the excessive accumulation of extracellular matrix (ECM), remains an unresolved problem in most forms of heart disease. In order to be successful in preventing, attenuating or reversing cardiac fibrosis, it is essential to understand the processes leading to ECM production and accumulation. Cardiac fibroblasts are the main producers of cardiac ECM, and harbor great phenotypic plasticity. They are activated by the disease-associated changes in mechanical properties of the heart, including stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
123
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(131 citation statements)
references
References 280 publications
(394 reference statements)
4
123
0
Order By: Relevance
“…Fibroblasts are highly responsive to post-infarct biochemical cues consisting of pro-inflammatory cytokines, growth factors, and hormonal agents that stimulate fibroblasts to degrade or deposit ECM. A growing body of research has also shown that fibroblast functionality is dependent on local mechanical cues; MI-induced loss of cardiomyocytes results in increased circumferential stretch at the infarct [5,6], which stimulates fibroblast activation through several mechano-sensing mechanisms [7]. While biochemical and mechanical signaling pathways have been studied individually in cardiac fibroblasts, few studies have examined the interplay between biochemical and mechanical signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblasts are highly responsive to post-infarct biochemical cues consisting of pro-inflammatory cytokines, growth factors, and hormonal agents that stimulate fibroblasts to degrade or deposit ECM. A growing body of research has also shown that fibroblast functionality is dependent on local mechanical cues; MI-induced loss of cardiomyocytes results in increased circumferential stretch at the infarct [5,6], which stimulates fibroblast activation through several mechano-sensing mechanisms [7]. While biochemical and mechanical signaling pathways have been studied individually in cardiac fibroblasts, few studies have examined the interplay between biochemical and mechanical signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Our observation that Piezo1 opposes myofibroblast differentiation is intriguing as mechanical stimulation is known to be an important driver of myofibroblast differentiation which, along with TGF-β, induces changes in gene expression including upregulation of α-SMA. Activation of integrins, TRP channels and cytoskeletal complexes have been shown to translate mechanical signals into changes in cardiac fibroblast gene expression including those involved in myofibroblast differentiation [4,5]. However, our data suggest that Piezo1 acts to oppose these signals.…”
Section: Discussionmentioning
confidence: 59%
“…Much remains unknown regarding how mechanical forces are translated into transcriptional responses important for determination of the fibroblast phenotype and how this can lead to cardiac remodeling [4,5]. Stretch-activated ion channels have been identified as candidates for cardiac mechanotransducers [6].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac fibroblast activation is affected by mechanical cues through direct translation of cytoskeleton tensioning into intracellular activation cascades or by controlling the release of paracrine signals [42]. For example, the persistent elevated stretch of mice cardiac fibroblasts, mimicking the mechanics of the infarct region, stimulates sustained production of ECM, causing myocardial stiffening [43] (Figure 3). Moreover, matrix hardening associated with infarct scar maturation induces cell spreading, formation of smooth muscle α-actin stress fiber and expression of collagens I/III [42,43].…”
Section: Role Of Mechanical Factors In Myofibroblast Activation and Cmentioning
confidence: 99%
“…For example, the persistent elevated stretch of mice cardiac fibroblasts, mimicking the mechanics of the infarct region, stimulates sustained production of ECM, causing myocardial stiffening [43] (Figure 3). Moreover, matrix hardening associated with infarct scar maturation induces cell spreading, formation of smooth muscle α-actin stress fiber and expression of collagens I/III [42,43]. The complex YAP/TAZ, involved in cell mechanosensing [44], exerts a crucial role in adult cardiac fibroblasts migration, proliferation and differentiation [45].…”
Section: Role Of Mechanical Factors In Myofibroblast Activation and Cmentioning
confidence: 99%